A lei de segurança privada no Brasil e a lei de atividade de segurança privada de Portugal - Trento, Abner Sousa (2022)
The purpose of this master thesis is to understand how private security is structured in Portugal and in Brazil, highlighting the provision of services of private security activity to banks. Through a comparative analysis focused on the evolution of the activity of private security in Brazil and in Portugal, this thesis aims to highlight omissions and loopholes in the legislation of that countries, presenting solutions to increase the list of private security activities, as well proposing improvements for the private security activities in Banks and Financial Institutions.